Voice and Frames in the Soviet Nenets’ Auto/Biographies - Lukin, Karina (European Journal of Life Writing, 2020)
This article explores the narrative and metalinguistic devices used by two Nenets writers, Nikolaj Vylka and Anton Pyrerka, in the auto/ biographical novels they wrote in the Soviet Union in the 1930s. Focusing on narrator roles and voices, the article argues that despite the overarching programme of socialist realism, the writers creatively used available linguistic resources to build Socialist plots and frames in their novels. However, their choices differ considerably, reflecting their divergent ideas about the relationship between pre- and post-Soviet Nenets culture.